KAJIAN KUALITATIF FAKTOR INTERNAL YANG MEMPENGARUHI KEHAMILAN REMAJA DI KECAMATAN INDRAMAYU KABUPATEN INDRAMAYU - Aryanti, Mira; Apriliani, Purwandyarti; Anggita, Intan; Murni, Dewi Eka Stia (Jurnal Ilmiah Bidan (JIB), 2022)
Background: Teenage pregnancy is a pregnancy in women aged 11-19 years. Pregnancy at a young age increases the risk for both mother and child. Babies born to teenage mothers are more likely to have low birth weight (LBW) with a risk of long-term effects. Pregnancy and childbirth complications are the causes of death for adolescent mothers aged 15-19 years. The Maternal Mortality Rate (MMR) in Indramayu in 2018 there were 61 cases while the Infant Mortality Rate (IMR) in Indramayu in 2018 there were 242 cases. Data on teenage pregnancies at the Puskesmas in the Indramayu District area from January to May 2019 were 36 cases. Puskesmas Margadadi and Puskesmas Plumbon are puskesmas located in the working area of ​​the Indramayu sub-district which is located in the city area, with many cases of teenage pregnancy in urban areas one of the reasons is the large number of junior high and high school schools and equivalent, and many migrants who will continue in the region city. The research objective was to analyze internal factors that could affect teenage pregnancy in Indramayu District, Indramayu Regency Methods: Qualitative research using in-depth interviews. The sample used was 8 pregnant women aged 11-19 years who met the inclusion criteria and did not meet the exclusion criteria. Research time is November 2019-January 2020. Results: The factors that influence teenage pregnancy in Indramayu District, Indramayu Regency include biological factors which include desire for sexual intercourse, cognitive factors which include apriori education and teenage marriage. Conclusion: Internal factors that influence teenage pregnancy in Indramayu District, Indramayu Regency are Biological factors, cognitive factors and adolescent marriage.